Pengaruh Struktur Modal Dan Profitability Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Pemoderasi - Dewi, Elawati; Akhmadi, Akhmadi (GEMA EKONOMI, 2023)
The purpose of this study is to examine the impact of capital structure and profitability on firm value moderated by dividend policy in industrial sector companies. The approach used in this research is a quantitative approach. The sample in this study were 8 companies in the chemical industry sector that were listed on the IDX in the period 2015 - 2021. The research data is secondary data which is then processed using the panel regression analysis technique. Panel regression results show that capital structure has a positive impact on firm value, profitability has a positive impact on firm value, dividend policy can weaken the impact of capital structure on firm value but dividend policy does not moderate the impact of firm profitability on firm value, companies with the right capital structure will have firm value which is not good if the company implements a large company dividend distribution while on the relationship between company profitability and company value, both companies with low and high dividend policies, the effect of profitability on company value is equally strong